(untitled) (Світ фінансів, 2017)
Васильчишин О. Б. Проблеми розвитку франчайзингового механізму в Україні. Розкрито теоретичні й практичні аспекти функціонування франчайзингового механізму. Проаналізовано переваги та недоліки його використання. Визначено тенденції розвитку франчайзингу в зарубіжних країнах та особливості його функціонуванняв Україні.Визначенопричини, що стримують розвиток франчайзингу, й наголошено на необхідності активізації діяльності банківських установ як важливої передумови розвитку франчайзингу в Україні. Vasylchyshyn O. The Problems of Franchising Mechanism Development in Ukraine. The separate theoretical and practical questions of functioning of franchayzing mechanism are considered. Advantages and lacks of his use are analysed. The tendencies of development of franchayzing are definite in foreign countries and feature of functioning of him in Ukraine. Reasons that restrain development of franchayzing and the necessity of activation of activity of bank institutions is marked as important precondition of development of franchayzing in Ukraine are definite.